The Astronaut's Cookbook Tales, Recipes, and More - Bourland, Charles T.; Vogt, Gregory L.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Ever wanted to know what the astronauts eat when they$1 (Bre in space? Now, you can do better than that! You can actually make what they eat in your own kitchen! And while you$1 (Bre waiting for your delicious (hah!) space food to cook, you can read about the history of the space program, space food preparation methods, and even get to know many of the astronauts that have dined in space. Did they find the food appetizing? What did they miss most when they were in space? How did NASA try to improve the food over the years? Charles Bourland is a retired long-time director of the NASA space food program, and Gregory Vogt, also a former NASA education specialist, helped train the astronauts. Both veterans of the U.S. space program have combined here to provide authentic recipes not only of foods that were actually served during various space missions (including Skylab, Apollo, the space shuttle, and the International Space Station) but also some of the astronauts$1 (Bfavorite recipes and even space recipes from famous TV chefs Rachael Ray and Emeril Lagasse! You will be amused and amazed at the information you find here. And you will be ready to impress your friends and family with your new culinary skills. Finally, you will have a much better understanding of what it really is to live in space, for weeks or even months at a time. Any volunteers for a trip to Mars? If you are a food lover, maybe not after you read this book and serve up some of its culinary treats$1! =s
Breakfast Foods -- Snacks and Appetizers -- Soups and Salads -- Bread, Tortillas, and Sandwiches -- Main Dishes -- Eat Your Vegetables! -- Desserts -- Beverages -- Future Space Food.
Keywords: Science (General).; Astronomy; Astronautics; Popular Science; Popular Science, general; Astronomy, Observations and Techniques; Popular Science in Astronomy; Aerospace Technology and Astronautics